Design of the Management Information System for Interns at the Communication and Information Service of East Kalimantan Province - Karyn, Alesandra Gabriella; Pahrudin, Pajar; Khair, Ahmad Abul (IJISTECH (International Journal of Information System and Technology), 2025)
This study aims to design an integrated, web-based Internship Management Information System specifically for the Department of Communication and Informatics of East Kalimantan Province. The background of this research lies in the existing manual internship administration process, including participant registration, document verification, daily attendance recording, performance evaluation, and certificate issuance, all of which are time-consuming and prone to errors. The research adopts the System Development Life Cycle (SDLC) with the Waterfall model, encompassing requirements analysis, system design, and the development of user interface mockups, without proceeding to actual system implementation. Requirements analysis was conducted through literature review, observation, and interviews with stakeholders to formulate the functional and non-functional needs of the system. The result is a comprehensive system blueprint, consisting of main process flowcharts, UML diagrams (use case, class, activity), and user interface designs for admins, participants, and supervisors. The system design enables online registration, digital data verification, daily reporting by participants, real-time monitoring by supervisors, automated evaluation based on specific criteria, as well as digital certificate generation and verification by the admin. This blueprint is expected not only to accelerate and simplify the internship process but also to enhance transparency, accountability, and efficiency in talent data management within the Department of Communication and Informatics of East Kalimantan Province. Furthermore, the system design can serve as a model for developing similar applications in other government agencies.